Faktor-Faktor Yang Mempengaruhi Kepatuhan Wajib Pajak Badan Pada Kantor Pajak Pratama Tanjung Karang - yeni anggraeni; kusnadi kusnadi; eka sariningsih (Universitas Malahayati, 2022)
Tax is a mandatory contribution to the state owed by every person or entity that is forced but still based on the Act. The minimum level of compliance of taxpayers causes, among others, taxpayers still perceive taxes as mandatory levies because they do not yet have a high awareness so that taxes are assessed as burdens. This study aims to provide relevant evidence of any of these ten factors, which affect taxpayer compliance in the Tanjung Karang Bandar Lampung KPP. This study uses primary data obtained from questionnaires. The population in this study are taxpayers who are active in the Bandar Lampung Primary Tax Office. The number of samples taken was 355 respondents. Analysis of the data used is multiple linear analysis. The results showed knowledge and environmental variables that had an effect on and significant on tax compliance, while other variables had no effect.Keywords : Attitude, Age, gender, knowledge, financial condition, environment, morals, sanctions, E-system and Socialization